Climbing plants of a fragmented area of lowland Atlantic Forest, Igarassu, Pernambuco (northeastern Brazil) - Araujo, D.; Alves, M. (Phytotaxa, 2014)
This study was undertaken in fragments of lowland Atlantic Forest surrounded by sugar cane plantations in Igarassu, Pernambuco, Brazil. Amongst the 93 species recorded for the locality, 30 species have a climbing habit. Passiflora is among the most species-rich genera which is novel in a floristic study. Morphological characters such as the presence and position of a tendril, limb form and flower symmetry are the most important for species identification. Here we present a species checklist for the locality, annotated with distribution data. An illustrated key to the climbing species found in Igarassu is also provided.